The Sepsis in Obstetrics Score: A Model to Identify Risk of Morbidity From Sepsis in Pregnancy. Issue 3 (September 2015) - Albright, C.M.; Ali, T.N.; Lopes, V.; Rouse, D.J.; Anderson, B.L.
Abstract : ( Am J Obstet Gynecol . 2014;211:39.e1–39e8)